POWER RELATIONS IN THE CONTEXT OF GENDER - AKGÜL, Fatma İlknur (SSD Journal, 2021)
While human beings are born as male and female due to their biological nature, in the process of socialization, they get rid of this state of existence and receive the man and woman molds called "gender". Through that process different meanings related to manhood and womanhood are developed within the value system and different roles are assigned to them in social life. It is a matter of fact that power relations lie at the basis of the social meaning attributed to human beings. Power emerges through social relations and is seen in all spheres of social life. Wherever it occurs, it brings the relationship between superior and subordinate. Any relations that seem to complement each other actually nurture power relations. While one of the actors in the relationship is dominant and superior, the other is in a dependent and secondary position. In the process of constructing itself, the power develops its understanding of gender through devices such as language, religion, culture, authority, discourse and social relations. This study discusses how power relations are reproduced and maintained through the construction of gender and gender roles. It will firstly analyze the meaning attached to the concepts of gender and power and then will focus on the relationship between them.